Parent Perspectives of Ear Health and the Relationship with Children’s Speech and Language in the Longitudinal Study of Indigenous Children - Anita Morrow; Neil Orr; Kai Nash; Harvey Coates; Cara Cross; John Robert Evans; Hasantha Gunasekera; Samantha Harkus; Linda Harrison; Sharynne McLeod; Catherine McMahon; Katie Neal; et al. (Children, 2023)
Health and well-being are holistic concepts that are perceived to be inseparable for Aboriginal and Torres Strait Islander peoples. We examined relationships between parent-reported ear symptoms for 787 Indigenous children at two time points (age 2–3 years, age 4–5 years) and two parent-reported speech and language outcomes one year later (age 5–6 years). Most parents (80.2%) reported no concern about their child’s expressive language and (93.8%) receptive language. Binary logistic regression models examined ear health as a predictor of children’s expressive and receptive speech and language adjusting for sociodemographic and health covariates. For children without parent-reported ear symptoms, there were lower odds of parental concern about expressive speech and language (aOR = 0.45; 95% CI 0.21–0.99) and receptive language (aOR = 0.24; 95% CI 0.09–0.62). Parents were less likely to have concerns about the child’s expressive speech and language if their child was female, lived in urban or regional areas, had excellent or very good global health, or had no disability when aged 2–5 years. Since parent-reported ear health and speech and language concerns were related, Aboriginal and Torres Strait Islander children could benefit from culturally safe, strength-based, and family-centered integrated speech, language, and ear health services.